Spatial-temporal analysis of urban expansion in the municipality of Cajueiro da Praia – Piauí (Research, Society and Development, 2023)
The objective of the article is to analyze urban expansion and its driving factors in Cajueiro da Praia municipality over a period of 30 years (1990 to 2020). The land cover and land use mapping were conducted using data from the MapBiomas project's 7.1 collection, a tool that allows for temporal analysis of changes in the Brazilian territory. In this regard, nine classes of land cover and land use were defined, including urban areas, mangroves, beaches, dunes, aquaculture areas, and agricultural areas. The study utilized geoprocessing software such as Google Earth Engine (GEE) and QGIS to process and analyze the data. Subsequently, a line graph was generated to visualize the trend of urbanized area growth over the years, revealing a 151.88% increase in urban expansion. According to the results, it was observed that the process of urban expansion in the region was driven by factors such as increased tourism, real estate investments, and shrimp production development. The use of geotechnology tools proved to be effective in monitoring urban expansion and understanding the transformations that occurred in Cajueiro da Praia municipality during the study period.